Will AI Enable Synthetic Biology in Medicine? A New Era of Precision Health - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The convergence of Artificial Intelligence AI and synthetic biology is poised to redefine the landscape of modern medicine. Synthetic biology, the engineerin...
Keywords: Diagnostics; Artificial Intelligence; Precision Medicine; Machine Learning; Medical Ethics